PENGARUH IKLIM ORGANISASI DAN KOMUNIKASI INTERPERSONAL TERHADAP KOMITMEN ORGANISASI PADA KARYAWAN KANTOR PT. ANGKASA PURA II (PERSERO) BANDAR UDARA SULTAN SYARIF KASIM II PEKANBARU - Sari, Erna Widiya Prasetriyana; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to explain the influence of organizational climate and interpersonal communication on the organization's commitment to the employees of the office of PT. Angkasa Pura II (Persero) Airports Sultan Syarif Kasim II Pekanbaru. Organizational climate as a variable (X1), interpersonal communication as a variable (X2), and organizational commitment as a variable (Y). The method in this research is descriptive and quantitative research by using the program SPSS version 25 for windows, which were collected through questionnaires to 66 respondents. The samples used are employees of the office of PT. Angkasa Pura II (Persero) Pekanbaru and as a source of information is used to determine the sample HR census method.From the results of data analysis include validity, reliability, simple linear regression, multiple linear regression test, test of determination, t test, and test f. It can be concluded that the organizational climate significantly influence the organizational commitment of employees of the office of PT. Angkasa Pura II (Persero) Airports Sultan Syarif Kasim II Pekanbaru, interpersonal communication significantly influence the organizational commitment of employees of the office of PT. Angkasa Pura II (Persero) Airports Sultan Syarif Kasim II Pekanbaru, organizational climate and interpersonal communication significantly influence the organizational commitment of employees of the office of PT. Angkasa Pura II (Persero) Airports Sultan Syarif Kasim II Pekanbaru. Keywords: Climate Organizational, Interpersonal Communication, and Organizational Commitment